The Effect of a Psychological Counseling Program Supported by Artificial Intelligence Applications on Enhancing Mental Training and Developing Setting and Spiking Skills in Sitting Volleyball Players - Salman, Suhair Rahman (JURNAL PENDIDIKAN OLAHRAGA, 2025)
The problem is that the training programs currently in place lack modern psychological counseling methods and do not utilize artificial intelligence applications in a way that enhances players' mental and psychological abilities. Objectives: To identify the impact of a counseling program supported by artificial intelligence applications on enhancing mental training and developing the skills of preparation and smashing for sitting volleyball players between the control and experimental groups. To identify the differences in the mental training scale and the development of the skills of preparation and smashing for sitting volleyball players between the pre- and post-tests of the control and experimental groups. Materials and Methods: To achieve the objectives, the researcher used an experimental approach with two groups, an experimental and a control, and a descriptive approach to the study's scale. The population consisted of (67) sitting volleyball players from clubs in the southern governorates for the 2024-2025 sports season. The main sample consisted of (16) players divided into a control group using the coach's curriculum and an experimental group using the coach's curriculum with counseling sessions designed by the researcher. Results: The experimental group outperformed the control group in enhancing mental training and developing the skills under study. Conclusions: Artificial intelligence technology contributes to the development of an advanced system for training athletes. Visual imagination based on artificial intelligence generates diverse ideas that help facilitate performance, develop creativity, and highlight its role.